Peat bogs as archives of atmospheric metal pollution from natural and anthropogenic sources - A case study from Ireland - ROSCA, CAROLINA (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2018)
This research project combines various geochemical techniques to identify and characterise historic and recent sources of atmospheric metal pollution recorded in ombrotrophic peat bogs across Ireland. In a first subproject, trace element concentrations and Pb isotope signatures are used to investigate a peat monolith from the Liffey Head bog in the Wicklow Mountains (Co. Wicklow, eastern Ireland). The results show significant heavy metal (Cu, Zn, Pb, Ag, Sb, Sn, Cd) perturbance during the local Pb-Zn mining and smelting activities (19th-20th century), with concentrations exceeding crustal abundances by far (e.g., 40-fold Pb, 80-fold Sb). Lead isotopes display the composition of the local lithology during the mining period of the 19th century (206Pb/207Pb=1.183±0.013) but shift towards significantly less radiogenic values (206Pb/207Pb=1.138±0.011) in 1980, reflecting the wider use of leaded petrol in the northern hemisphere. Remarkably, the highest Pb pollution at this site is not associated with the use of leaded petrol rather than the historic metalliferous activity in the Wicklow uplands. In the second subproject, evolution and sources of recent atmospheric metal pollution with emphasis on Zn are examined and compared in a near-urban environment (Liffey Head bog, Co. Wicklow, east coast) and a rural area (Brackloon wood, Co. Mayo, west coast of Ireland). A combination of trace metal systematics, radiogenic Pb- and stable Zn isotopes allows to distinguish pollution sources. A dominant influence from solid fossil fuel combustion (coal) can be inferred for west Ireland (Cr/Cd=12, Zn/Cd=96, at 0-1 cm) whereas increasing emissions from the wider deployment of liquid fossil fuels (oil, diesel, petrol) are recorded close to the urban area of Dublin in east Ireland (oil: Cu/Cd=57, Zn/Cd=300 at 0-1 cm). This interpretation is further supported by increasingly light Zn isotope signatures with sallower peat bog horizons (δ66Zn/64Zn= from 0.53 to 0.18 ±0.03‰), readily explained by stronger traffic emissions through recent time. In a third subproject, the geochemical record of the historic Laki 1783-4 volcanic eruption was identified and further examined in Brackloon wood peat bog horizons from western Ireland. This eruption record is expressed in excess metal concentrations of V, Ti, and Fe. Although these cannot unequivocally be attributed to an addition of basaltic cryptotephra at this depth, the higher concentrations of these elements in the separately investigated tephra shards compared to background peat support this hypothesis. Moreover, remarkably systematic correlations are observed for metal ratios such as Cu/Cd, Pb/Cd, Pb/Zn, Cu/Zn between the tephra-bearing layer and Laki aerosols previously detected in Greenland ice. These correlations point to a common volcanic aerosol signal originating from the Laki eruption. Although the high background in the peat monolith complicates a deconvolution of the S signal, subtle S enrichments at the depth of tephra deposition are attributed to addition of Laki 1783-4 volcanic aerosols. Altogether, the potential of peat bog archives to record volcanogenic metal deposition is demonstrated and dependent on background concentration levels.
APPROVED
Keywords: peatlands, ombrotrophic bogs, pollution, mining, fossil fuel burning, Pb isotopes, Zn isotopes